Differentiated Orders in Criminal Proceedings - I. Ju. Murashkin (Сибирское юридическое обозрение, 2014)
The author offers the definition and classification of the differentiated criminal proceedings orders, determines the place of special orders, proposes alterations in the criminal procedure legislation, excluding homonymy.